2014
DOI: 10.1242/jeb.101279
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory learning and memory in the disease vector mosquito,Aedes aegypti

Abstract: Olfactory learning in blood-feeding insects, such as mosquitoes, could play an important role in host preference and disease transmission. However, standardised protocols allowing testing of their learning abilities are currently lacking, and how different olfactory stimuli are learned by these insects remains unknown. Using a Pavlovian conditioning paradigm, we trained individuals and groups of Aedes aegypti mosquitoes to associate an odorant conditioned stimulus (CS) with a blood-reinforced thermal stimulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 64 publications
(83 reference statements)
1
61
0
Order By: Relevance
“…Since Charlwood et al 's study in Papua New Guinea [6] - possibly the first study to explicitly investigate memory in a vector - more recent studies have assessed the abilities of mosquitoes to perform associative learning (see Box 1) to visual and olfactory stimuli [13, 15-18], including some studies that failed to demonstrate learning [19]. In an example demonstrating aspects of associative learning in Cx.…”
Section: Recent Advances In Vector Learning and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Since Charlwood et al 's study in Papua New Guinea [6] - possibly the first study to explicitly investigate memory in a vector - more recent studies have assessed the abilities of mosquitoes to perform associative learning (see Box 1) to visual and olfactory stimuli [13, 15-18], including some studies that failed to demonstrate learning [19]. In an example demonstrating aspects of associative learning in Cx.…”
Section: Recent Advances In Vector Learning and Memorymentioning
confidence: 99%
“…Employing a training procedure that provided a high degree of temporal and quantitative control of the CS and US delivery, Vinauger et al [18] showed that Ae. aegypti mosquitoes can associate L-lactic acid, a host emitted volatile compound, with a blood-reward.…”
Section: Recent Advances In Vector Learning and Memorymentioning
confidence: 99%
“…They also imply that a potential control technique aimed specifically at young insects should work preferentially outdoors. Young, naïve mosquitoes may be attracted to a wider range of potential hosts than older insects, which may return to feed on hosts that they have fed on previously (Vantaux et al, 2014; Vinauger, Lutz & Riffell, 2014). Odour baited traps that target such young insects may be one possible approach.…”
Section: Discussionmentioning
confidence: 99%
“…To compare paired male performance within the same trial, relative orientation was calculated as θ a,male1 −θ a,male2 . We also computed a preference index (PI) for each male, in which PI=[number of sperm oriented towards the attractant (θ a <90 deg) −number of sperm oriented away from the attractant (θ a >90 deg)]/ (total number of sperm) (Vinauger et al, 2014). The index takes a value of PI=1 when all sperm are oriented towards the attractant and PI=−1 when all sperm are oriented away from the attractant.…”
Section: Chemotaxis Assays and Analysismentioning
confidence: 99%